DEVELOPMENT OF A CHANGE OF DIRECTION TRAINING MODEL FOR JUNIOR TENNIS ATHLETES - Yonda, Okki; Miftakhudin, Heru; Oktafiranda, Nadya Dwi; Yuliana, Ela (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This research aims to develop a Change of Direction (CoD) training model for junior tennis athletes. Developing a training model using the ADDIE approach (analysis, design, development, implementation, evaluation). In the fifth stage or evaluation, using a sample of 46, to determine the effectiveness of the CoD training model. The N-Gain Score test is used to determine the effectiveness of the CoD training model in junior tennis athletes. The research results showed that the average pretest was 17.66 sec, and after treatment (posttest) it was 17.02 sec. The results of the N-Gain Score test obtained an average value of 0.43, which means that the development of the CoD training model has moderate effectiveness in improving direction change skills in junior tennis athletes. Thus, the CoD training model developed can be applied to improve direction change skills in junior tennis athletes. Future research will need to determine the most effective form of training to improve athletes' change-of-direction skills, taking into account other factors that influence change-of-direction performance. So it can answer the challenge of how the CoD training method can significantly improve the ability to change direction and ultimately contribute to the performance of tennis athletes.